2004
DOI: 10.1139/s04-034
|View full text |Cite
|
Sign up to set email alerts
|

Friction and confinement effects on a shallow recirculating flow

Abstract: Experiments were conducted to study confinement and friction effects on a shallow recirculating flow that was formed in a lateral expansion of an open-channel flow on a smooth bed. Dye was introduced to the flow as tracer. The instantaneous dye concentration in the flow was captured by video simultaneously across the width and along the length of the flume. The mean and the root-mean-square values of the dye-concentration fluctuations at selected cross sections along the flow are analyzed and compared with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Increasing the bottom roughness up to k s = 0.005 m leads to hardly noticeable changes in the velocity profiles. Flow resistance remains indeed very weak, since the head loss across the reservoir is in any case of the order of 1 − 2 × 10 −4 m. These results are in agreement with Babarutsi et al (1989), Babarutsi andChu (1991) and Chu et al (2004) for unilateral expansions: since the bed friction number remains here lower than 0.05, the flow is classified as "non-frictional" and is thus not influenced by the roughness. In the L-L configuration (Fig.…”
Section: Velocity Profilessupporting
confidence: 81%
“…Increasing the bottom roughness up to k s = 0.005 m leads to hardly noticeable changes in the velocity profiles. Flow resistance remains indeed very weak, since the head loss across the reservoir is in any case of the order of 1 − 2 × 10 −4 m. These results are in agreement with Babarutsi et al (1989), Babarutsi andChu (1991) and Chu et al (2004) for unilateral expansions: since the bed friction number remains here lower than 0.05, the flow is classified as "non-frictional" and is thus not influenced by the roughness. In the L-L configuration (Fig.…”
Section: Velocity Profilessupporting
confidence: 81%
“…Several studies indicate that the length of the recirculation zone over unilateral expansions depends only on the lateral expansion for small values of the bed friction number; for large values, however, the reattachment length depends only on a friction length scale (Babarutsi et al 1989, Babarutsi and Chu 1991, Chu et al 2004). …”
Section: Froude Number F = U/(gh)mentioning
confidence: 99%
“…To the knowledge of the authors, only the median position has been reported in the literature, using, for example, visualization of displacement of confetti on the water surface (Babarutsi et al 1989, Babarutsi and Chu 1991, Chu et al 2004. Only Abbott and Kline (1962) characterized fluctuations of the reattachment lengths by carrying out a large number of tests.…”
mentioning
confidence: 99%
“…In the experiments, the reservoir boundary conditions were chosen to obtain flows with different friction regimes (frictional and non-frictional, see Chu et al (2004)) and the flow dynamics was quantified by LSPIV. The flows were then modelled using WOLF2D, which solves the shallow water equations and uses a depth-averaged k- turbulence model.…”
Section: Resultsmentioning
confidence: 99%
“…The friction numbers are characteristic of two different friction regimes. Referring to the work of Chu et al (2004), the flow-case F belongs to the frictional regime (the turbulence scale is mainly driven by the water depth), while the flow-case NF belong to the nonfrictional regime (the turbulence scale is mainly driven by the horizontal length-scale). The Reynolds numbers in both cases confirm that the flows are turbulent, but they are hydrodynamically smooth.…”
Section: Experimental Set-upmentioning
confidence: 99%